THE IMPORTANCE OF MIGRANT RIGHTS PROTECTION AT THE REPUBLICAN AND INTERNATIONAL LEVEL - Iqboloy Ummatova (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation. Within the framework of this article, the author highlighted the importance of external migration and its status, local and international organizations protecting migrant rights and regulatory legal acts. Also, statistics on migration have been analyzed and talk about achievements and shortcomings in this area. The article also covers the theoretical aspect of the concept of migration in detail.